Exposure and reach of the US court-mandated corrective statements advertising campaign on broadcast and social media. Issue 4 (21st June 2019) - Kostygina, Ganna; Szczypka, Glen; Tran, Hy; Binns, Steven; Emery, Sherry L; Vallone, Donna; Hair, Elizabeth C
Abstract : Objective: As a remedy to committing fraud and violating civil racketeering laws, in November 2017, four major tobacco companies were court-ordered to develop and disseminate corrective statements regarding smoking health risks using mass media channels. We aimed to describe the nature, timing, reach of and exposure to the court-mandated tobacco industry corrective advertising campaign on social, broadcast and print media. Methods: Data from social, print and broadcast media were used to measure potential exposure to corrective messages. Keyword rules were used to collect campaign-related posts from the Twitter Firehose between November 2017 and January 2018. Data were analysed using a combination of machine learning, keyword algorithms and human coding. Posts were categorised by source (commercial/institutional, organic) and content type (eg, sentiment). Analysis of social media data was triangulated with ratings data for television advertising and print advertising expenditure data. Results: Keyword filters retrieved 13 846 tweets posted by 9232 unique users. The majority of tweets were posted by institutional/commercial sources including news organisations, bots and tobacco control-related accounts and contained links to news and public health-related websites. Approximately 60% of campaign-related tweets were posted during the first week of campaign launch. Household exposure to the televised corrective advertisements averaged 0.56 ads per month. Discussion: The corrective campaign failed to generate social media engagement. The size and timing of the advertising buys were not consistent with strategies effective in generating high sustained impact and audience reach, particularly among youth.